Prioritising conservation actions towards the sustainability of the dehesa by integrating the demands of society. (March 2023) - Parra-López, Carlos; Sayadi, Samir; Garcia-Garcia, Guillermo; Ben Abdallah, Saker; Carmona-Torres, Carmen
Abstract: CONTEXT: The dehesa is an important agrosilvopastoral system in the Mediterranean, consisting of trees, livestock and pasture. It is a multifunctional system that offers a wide range of products and services, including food and forest products, as well as environmental and social services. However, this ecosystem is vulnerable in Andalusia, southern Spain, due to its low economic profitability and environmental and social challenges. OBJECTIVE: To contribute to the design of public policies towards greater sustainability of the Andalusian dehesa. For this purpose, different conservation actions/sub-actions (CAs/CSs), i.e. agroforestry and pastoral practices, were evaluated and prioritised according to their expected contribution to sustainability. METHODS: A multi-criteria model based on the Analytical Hierarchy Process (AHP) is developed to prioritise the environmental, economic and social demands of Andalusian society. It also allows estimating the contribution of CAs/CSs to the different functions of the dehesa and to the demands of society. The model is assessed on the basis of a survey of society in the dehesa areas of Andalusia and the knowledge of dehesa experts. RESULTS AND CONCLUSIONS: Society prioritises the environmental dimension of the dehesa. Thus, among society's demands, the highest priorities are the production of typical and quality landscapes and the conservation of biodiversity. In terms of the functions of the dehesa, the social ones stand out for their contribution to sustainability, especially the preservation of cultural heritage. After the social functions, forest production (economic function) and biodiversity (environmental function) are the highest priority functions. For the CAs, soil and water conservation and the renewal of trees are the highest priorities for improving the sustainability of the dehesa. Finally, the most critical CSs have also been identified as those with the greatest potential to improve sustainability based on current practices. SIGNIFICANCE: The methodology/model proposed for the design of policies to improve the sustainability of the Andalusian dehesa allowed the demands of society to be integrated into the process, understanding sustainability to be associated with the general well-being of society. The methodology can serve as a guide for assessing the sustainability associated with management actions in other agricultural systems and/or regions. Furthermore, the results obtained can contribute to the design of public policies towards greater sustainability of the dehesa not only in Andalusia, but also in other regions. The results highlight the importance of considering the productive and non-productive functions of the dehesa as a whole when designing public policies towards sustainability. Graphical abstract: Unlabelled Image Highlights: The dehesa plays an important economic, environmental and social role in the Mediterranean; This agrosilvopastoral system is very vulnerable in Andalusia, in southern Spain, and its sustainability needs to be increased; The highest priority demands of society are the production of typical and quality landscapes and the conservation of biodiversity; Social functions, especially the conservation of cultural heritage, are the highest priority global functions of the dehesa; Soil and water conservation and renewal of trees are priority conservation actions to improve the sustainability of the dehesa.